(untitled) (Washington, D.C., 2009)
"Distortions to Agricultural Incentives in Asia" is the third volume in a series of books that brings together analytical narratives of the evolution over the past half - century of policy - imposed distortions to farmer incentives and food prices in 80 countries. Drawing on new consistent set of estimates spanning 90 percent of the world's agricultural markets, the first two titles in the series focus on Europe's transitional economies and Latin America. Future titles will focus on Africa and the distortions to agricultural incentives from a global perspective.
Keywords: Agriculture,Nông nghiệp,Agricultural subsidies,Agriculture and state,Trợ cấp nông nghiệp; Economic aspects,Khía cạnh kinh tế; Asia,Châu Á,Asia,Asia,Châu Á